CADEIAS DO AGRONEGÓCIO DE ALIMENTOS DA REGIÃO FRONTEIRA NOROESTE DO RIO GRANDE DO SUL - Graef, Nelinho D.; Weisner, Aline; Büttenbender, Pedro L.; Zamberlan, Luciano; Sparemberger, Ariosto; Höfler, Claudio E. (Salão do Conhecimento, 2013)
Resumo